2014
DOI: 10.1089/bfm.2013.0092
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Infants with Phenylketonuria in the United States and Canada

Abstract: Objective: This study described the prevalence and duration of mothers' breastfeeding infants with phenylketonuria (PKU) and explored factors related to duration of breastfeeding as a surrogate for breastfeeding success. Subjects and Methods: Descriptive analysis as performed from an international Internet survey of mothers (n = 103) who met the inclusion criteria: (1) at least 21 years of age, (2) able to read and write in English, (3) child with PKU, and (4) living in the United States or Canada. Results: Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
2
13
0
4
Order By: Relevance
“…Initially 89 mothers breastfed, but after the diagnosis, only 72 mothers continued to breastfeed. This decrease was significant (McNemar's χ 2 = 30.333, p < .001; n = 72 vs. n = 89) (Banta‐Wright et al., ).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Initially 89 mothers breastfed, but after the diagnosis, only 72 mothers continued to breastfeed. This decrease was significant (McNemar's χ 2 = 30.333, p < .001; n = 72 vs. n = 89) (Banta‐Wright et al., ).…”
Section: Methodsmentioning
confidence: 96%
“…Although many mothers successfully continue to breastfeed, many mothers decide not to continue to breastfeed after the diagnosis of PKU (Banta-Wright, Press, Knafl, Steiner, & Houck, 2014). In addition, investigators have consistently reported that few mothers of infants with PKU persist in breastfeeding beyond an initial period and breastfeed for a shorter duration than mothers of other healthy term infants (Agostoni, Verduci, Fiori, Riva, & Giovannini, 2000;Banta-Wright et al, 2014;Banta-Wright, Shelton, Lowe, Knafl, & Houck, Breastfeeding infants with phenylketonuria is challenging in part because it is virtually impossible to precisely determine phenylalanine intake. Cornejo et al, 2003;Demirkol et al, 2001;Huner & Demirkol, 1996;Kanufre et al, 2007;Motzfeldt et al, 1999;Segev, Abraham, Anikster, & Schwartz, 2004;van Rijn et al, 2003).…”
mentioning
confidence: 99%
“…Respondents in this analysis also were participants in the larger study examining the prevalence and duration of breastfeeding infants with PKU (Banta-Wright et al, 2014). Demographic characteristics of the mothers and infants in this report are presented in Tables 1 and 2 respectively.…”
Section: Samplementioning
confidence: 99%
“…Similarly, a Brazilian study reported that slightly more than half of the mothers were breastfeeding their infants with PKU at 6 months and by 12 months less than a third continued to breastfeed (Kanufre et al, 2007). In a more recent study involving mothers from the United States and Canada, the prevalence of breastfeeding infants with PKU before and after diagnosis revealed that significantly few mothers continued to breastfeed after diagnosis (Banta-Wright et al, 2014). Overall, the incidence, prevalence, and duration of breastfeeding when infants have PKU continue to be less than when full-term infants do not have PKU (Agostoni et al, 2000;Banta-Wright et al, 2014;Kanufre et al, 2007;Motzfeldt et al, 1999;Segev et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation